2019
DOI: 10.31486/toj.18.0046
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Ventricular Tachycardia From Coronary Vasospasm During Pregnancy

Abstract: Background: Coronary vasospasm leading to variant angina is uncommon, and the condition is rare in pregnant patients. Many physiologic changes occur during pregnancy, but how these changes affect the spasticity of coronary arteries in patients predisposed to vasospasm is unknown. Vasospasm causing unstable arrhythmia from multiple foci can be difficult to treat.Case Report: A 22-year-old gravida 1 para 0 female at 17 weeks’ gestation with twins presented with chest pain refractory to sublingual nitroglycerin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In pregnant women, it has been suggested that hormonal and nervous system changes that occur during pregnancy seem to trigger VSA. 3 Exposure to pain stress, hyperventilation-induced alkalosis, and administration of methylergometrine for flaccid hemostasis can further induce a vasospasm attack. Several studies have reported that VSA plays a role in acute myocardial infarction occurring in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant women, it has been suggested that hormonal and nervous system changes that occur during pregnancy seem to trigger VSA. 3 Exposure to pain stress, hyperventilation-induced alkalosis, and administration of methylergometrine for flaccid hemostasis can further induce a vasospasm attack. Several studies have reported that VSA plays a role in acute myocardial infarction occurring in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“… 2 A previously published case describes increased episodes of coronary vasospasm during pregnancy with refractory ventricular arrhythmias requiring high-dose medications and chemical sympathectomy for management. 3 Identification of epicardial coronary disease or microvascular dysfunction would have prompted initiation of antiplatelet therapy, a nitrate, and a beta blocker. A statin would be added after delivery and breastfeeding.…”
Section: Question 2: How Does the Classification Of Her Initial Acs I...mentioning
confidence: 99%
“…This condition stems from occlusive or sub-occlusive coronary artery spasms, with endothelial dysfunction and diminished nitric oxide secretion serving as pivotal pathophysiological factors [ 1 ]. Notably, modifiable risk factors include smoking, while associations exist with male sex, magnesium deficiency, alcohol consumption, physical and mental stress, and autonomic nervous system agents [ 2 ]. Besides the classic presentation of variant angina, coronary artery vasospasm can manifest atypically, leading to acute myocardial infarction (AMI), fatal arrhythmias (e.g., ventricular tachycardia/fibrillation (VT/VF), complete atrioventricular block (AV-B)), or sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%